PENGARUH PENEMPATAN KARYAWAN DAN KOMPENSASI TERHADAP KOMPETENSI KARYAWAN PADA UNIT KONVEKSI PRIMKOPAD BEKANGDAM III / SLW - Irawan, Andri (Jurnal Manajemen dan Keuangan, 2010)
The purpose of this study was to determine the extent of the impact of staffing and compensation of employees competence and their implications for methods of personnel working in the unit "Convection" from Primkopad Bekangdam III / SLW. In this research, authors use an analysis of the data-analysis where data are taken based on the population of 54 employees at Primkopad Bekangdam Convection Unit III / Slw and in the determination of samples researcher using the sample consideration is to include all members of the population as a sample for the purpose of completeness dataBased on the processing of the first structure by using path-analysis, found that the placement of employees have a significant impact of partial and 51.6%, while compensation is not impartial and give only a less significant impact that is only 13.9%. However, simultaneous placement and compensation of employees has a simultaneous impactof32.5%andsignificant.Keyword: Staffing, compensation, and competence